Development of the B cell cancer vaccine HER-vaxx for the treatment of her-2 expressing cancers - Ede, Nicholas J.; Good, Anthony J.; Tobias, Joshua; Garner-Spitzer, Erika; Zielinski, Christoph C.; Wiedermann, Ursula (Frontiers in Oncology, 2022)
Her 2/neu is a tumor-associated protein that is overexpressed in a number of malignancies, including advanced cancer of the stomach, and has been proposed as a human cancer vaccine target. Overexpression of Her-2/neu in human breast and gastric carcinomas correlates with a more aggressive course of disease that results in poorer overall survival rates and shorter times to disease progression than in patients with tumors without overexpression of Her-2/neu. Cancer vaccines have the ability to stimulate the native immune system and in particular engineered B cell epitopes can elicit high affinity polyclonal antibodies with similar efficacy to Her-2 monoclonal antibodies such as trastuzumab (Roche). HER-Vaxx is under development as a therapeutic B cell vaccine for the treatment of gastric cancer in patients with Her-2/neu overexpressing metastatic or advanced adenocarcinoma of the stomach or gastroesophageal junction, referred to as advanced cancer of the stomach. P467-CRM197, the vaccine’s immunogenic component, contains a single peptide antigen composed of 3 individual linear B cell epitope peptide sequences selected from the oncoprotein Her-2/neu that induce the patient’s own B cells to produce endogenous anti-Her-2/neu antibodies. This review provides results from comprehensive preclinical studies encompassing primary and secondary pharmacodynamics, biodistribution and safety studies. These studies were performed to support clinical development of HER-Vaxx. Results from the GLP toxicology study in rodents showed that the vaccine did not produce any observable adverse effects suggesting that the doses proposed for the clinical trial should be well tolerated in patients.